2016
DOI: 10.4103/2278-330x.181624
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the results of a triplet metronomic chemotherapy regimen incorporating a tyrosine kinase inhibitor in recurrent/metastatic head and neck cancers patients

Abstract: Background:Addition of erlotinib to metronomic chemotherapy (MCT) may lead to further improvement in progression-free survival (PFS) and overall survival in head and neck cancers. The aim of this study was to study the PFS with MCT + erlotinib combination in our setting.Methods:A single-arm prospective observational study conducted at Malabar Cancer Center. Patients warranting palliative chemotherapy for head and neck cancers, having adequate organ function, not-affording cetuximab and not willing for intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…For head and neck cancer, another study evaluated metronomic oral regimen of methotrexate, erlotinib, and celecoxib in palliative treatment of patients with head and neck cancers and ineligible for MTD. Reported median PFS was 148 days [244]. Same authors retrospectively evaluated the adequacy of oral low dose chemotherapy for palliative treatment in a heterogenous group of head and neck cancer patients, revealing median OS of 155 days with oral cancers having a tendency for a shorter OS [245].…”
Section: Resultsmentioning
confidence: 99%
“…For head and neck cancer, another study evaluated metronomic oral regimen of methotrexate, erlotinib, and celecoxib in palliative treatment of patients with head and neck cancers and ineligible for MTD. Reported median PFS was 148 days [244]. Same authors retrospectively evaluated the adequacy of oral low dose chemotherapy for palliative treatment in a heterogenous group of head and neck cancer patients, revealing median OS of 155 days with oral cancers having a tendency for a shorter OS [245].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic of 13 selected studies were shown in Table 1[more details see Additional le 2]. The sample size ranged from 15 [23] to 422 [17] participants while median age differed from 41 [21] to 65 [23] years. In terms of tumor location, oral cavity occupied the most proportion, and next were pharynx and larynx.…”
Section: Study Characteristicmentioning
confidence: 99%
“…Regarding the remaining studies, two got 10 points, one for 8 points, four for 7, one for 6 and 5 respectively. Thus, three [21,23,24] were high quality and six [22,[25][26][27][28][29]…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Thus, addition of erlotinib showed promising results in improving PFS, but proper selection of patients is essential as 40% had Grade III/IV toxicity. [16] Mateen et al [17] presented their experience with MC in recurrent HNSCC. A total of 72 patients were enrolled and were prescribed oral methotrexate 2.5 mg twice in a week and capecitabine 500 mg twice a day, for at least 6 months.…”
Section: In Palliative Settingsmentioning
confidence: 99%